Can short-term memory capacity change resting brain behavior? Findings from neuropsychological assessment and dynamic causal modeling - Dzulkifli, Mariam Adawiah; Othman, Elza Azri; Mohamad, Mazlyfarina; Abdul Manan, Hanani; Abd Hamid, Aini Ismafairus (Routledge Taylor & Francis Group, 2025)
This study aimed to investigate different short-term memory capacities (STMC) on resting brain of healthy individuals particularly the neuropsychology and connectivity behaviors. The outcomes may serve as a baseline for clinical diagnosis of memory decline due to aging and mental disorders. It was hypothesized that resting brain of low and typical STMC individuals behaves differently. Thirty-nine healthy young male adults were recruited from local universities. They were categorized as typical or low STMC based on their scores in the Malay Version of the Auditory-Verbal Learning Test (MVAVLT). A resting-state functional magnetic resonance imaging (rs-fMRI) was conducted and data were analyzed using statistical parametric mapping (SPM) and dynamic causal modeling (DCM). Nine neuropsychological assessments were significantly higher (p<0.05) in typical STMC participants compared with low STMC participants. Four activation clusters survived the contrast “Low>Typical” uncorrected at set and cluster levels threshold (pFWE < 0.05). A causal model containing these clusters as nodes found that there is no preference on negative or positive connectivity among typical and low STMC groups. Nevertheless, implementing a reduced connection scheme revealed more significant connections for the low STMC group. To conclude, the low STMC participants scored lower in all neuropsychological assessments, but a higher activation profile with more areas being connected effectively as compared with the typical STMC group. The results suggest a higher resting neural activity and communication among certain brain areas in low STMC individuals that the brain could have executed as a compensation strategy.